Wire-sheet assembly construction of boron nitride/single-walled carbon nanotube shape-stabilized phase change composites for light-thermal energy conversion and storage. (March 2022) - Wu, Bojing; Zhang, Huanzhi; Huang, Chaowei; Zhang, Qingfeng; Sun, Zongxu; Xu, Fen; Sun, Lixian; Xia, Yongpeng; Peng, Hongliang; Lin, Xiangcheng; Zou, Yongjin; Chu, Hailiang; et al.
Highlights: Bulk composite PCMs were constructed by synergistic linear and sheet materials. The composite PCMs exhibit good energy storage capacity and thermal reliability. The prepared PCMs exhibit highly enhanced thermal conductivity of 0.92 W∙m −1 ∙K −1 . Light-to-heat conversion and storage is realized by 3D synergistic network. Abstract: As one of the most abundant energy, solar energy has already drawn great attention both from academia and industry, but how to use it to the utmost extent is still a formidable challenge for the development of human. Phase change material (PCM) is proved to be one of the most promising technique for storing thermal energy. Herein, we designed and fabricated a three-dimensional (3D) phase change composite (PCC) with excellent light-to-thermal conversion by constructing one-dimensional (1D) linear single-walled carbon nanotubes (SWNTs), two-dimensional (2D) boron nitride nanosheets (BNNSs) and polyethylene glycol (PEG) into a 3D bulk structure. This structure supplies the prepared PCMs with high thermal conductivity, excellent solar-thermal conversion efficiency, and high energy storage density. Results showed that the PCCs displayed a well-defined 3D interconnected structure, and their melting and crystallization enthalpies were 156.36 J/g and 153.33 J/g, respectively, which changed only slightly after 110 thermal cycles. The thermal conductivity of the composites could reach 0.92 W∙m −1 ∙K −1, which effectively enhanced the thermal response rate. Beyond that, the PCCs exhibited good leakage-proof performance and excellent thermal regulation performance. And the light-to-thermal conversion efficiency of PCCs reached 97.15%. These results indicate that this strategy can be efficiently used to develop novel PCCs with improved comprehensive thermal performances and high light-to-thermal conversion. Graphical abstract: Image, graphical abstract Novel shape-stabilized phase change composites were designed by synergistic assembly of one-dimensional (1D) linear single-walled carbon nanotubes (SWNTS), two-dimensional (2D) boron nitride (h-BN) and polyethylene glycol (PEG), which exhibit a 3D bulk structure, good solar-thermal conversion and storage capacity and high thermal conductivity.